2019
DOI: 10.3846/jbem.2019.9590
|View full text |Cite
|
Sign up to set email alerts
|

Tacit Knowledge and Firm Performance Relationship. The Role of Product Innovation and the Firm Level Capabilities

Abstract: Based on knowledge-based theory of organizational capabilities and dynamic capabilities theory, this paper tries to establish the linkages between tacit knowledge resources, its integration into firm level capabilities, product innovation and firm performance. In this way, the paper analyses the relationships between some of the most relevant variables to the organizations in order to remain competitive. The conceptual model is tested using a sample of organizations in the industrial sector, using SEM and hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 88 publications
(124 reference statements)
1
34
0
2
Order By: Relevance
“…Besides, the scientists in the papers [18][19][20][21][22][23] proved the linking between innovations, sustainable business model and country's competitiveness. The scientists in the papers [24][25][26][27][28][29] proved that sustainable business model could not be realised without innovations. The results of the analysis showed that the scientists analysed sustainable business model from the environmental, economic and social point of views.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the scientists in the papers [18][19][20][21][22][23] proved the linking between innovations, sustainable business model and country's competitiveness. The scientists in the papers [24][25][26][27][28][29] proved that sustainable business model could not be realised without innovations. The results of the analysis showed that the scientists analysed sustainable business model from the environmental, economic and social point of views.…”
Section: Introductionmentioning
confidence: 99%
“…We argue that TK contributes to OL and, in so doing, improves performance by encouraging the knowledge creation workforce to enhance the whole knowledge base of the organization for sustainable results. TK also contributes to financial performance (FP) to give organizations a competitive edge in the market (López-Cabarcos et al, 2019). However, research reports from the existing literature are rare and produce contradictory results on the relation between TK and FP (Donate & de Pablo, 2015;Song & Zhao, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, research reports from the existing literature are rare and produce contradictory results on the relation between TK and FP (Donate & de Pablo, 2015;Song & Zhao, 2019). Some researchers, like López-Cabarcos et al (2019) and Manaf et al (2018), believe that TK is implicitly tied to an organization's FP. This paradoxical clash illustrates the need for further research to expand practitioners' and scholars' understandings the relationship between TK and FP.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers began to probe for more details regarding the different aspects of knowledge relative to NPD success. Some examples of the knowledge base drivers of new product performance are as follows: market knowledge competence (Atuahene-Gima & Wei, 2011;Claudy, Peterson, & Pagell, 2016;Li & Calantone, 1998), exploiting external knowledge sources (Ferreras-Méndez, Newell, Fernández-Mesa, & Alegre, 2015), knowledge management (Lin, Che, & Ting, 2012), market knowledge dimensions (De Luca & Atuahene-Gima, 2007;Jin, Shu, & Zhou, 2019;López-Cabarcos, Srinivasan, Göttling-Oliveira-Monteiro, & Vázquez-Rodríguez, 2019), and knowledge integration mechanisms (De Luca & Atuahene-Gima, 2007;Guo, Cai, & Fei, 2019) or network-based market knowledge (Bao, Sheng, & Zhou, 2012). Knowledge is important in managing an organisation, and is recognised as another non-traditional production factor as well as a crucial resource for economic growth (Ginevičius & Korsakiene, 2005).…”
Section: Introductionmentioning
confidence: 99%